Roles of social learning for the adoption of climate-smart agriculture innovations: Case study from My Loi Climate-Smart Village, Vietnam - Tran, Helene; Simelton, Elisabeth; Quinn, Claire (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
With the rapid pace of climate change and its impact on food security and livelihoods, climate-smart agriculture is one strategy aiming to help farmers adopt more sustainable farming practices. This study looked at farmers’ adoption of agricultural innovations and the role of social networks in the process. Through interviews and observations, we (1) identified determinants and barriers affecting farmers’ adoption of agricultural innovations in My Loi Climate-Smart Village in northcentral Vietnam, and (2) explored how social learning and social networks contribute to farmers’ knowledge generation during innovation adoption. Results show that determinants and constraints for the adoption of agricultural innovation exist at multiple levels. The study presents evidence of the value of social networks for the adoption of innovation, identifies what constitutes promising social networks, and gives examples of institutional structures that influenced the adoption process. Recommendations for social learning networks and scaling of climate-smart agriculture innovations are provided.